2009
DOI: 10.2754/avb200978010137
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Safety of La Sota Strain of Newcastle Disease Virus Administered to Newly Hatched Chicks by Nebulization

Abstract: The objective of four trials performed on specific-pathogen-free and commercial chickens, either of light or heavy hybrids, was to evaluate the new vaccine delivery method to newly hatched chickens using commercial La Sota vaccine. The vaccine was given by means of nebulization using an ultrasonic device producing homologous aerosol of particles ranging 3-5 microns in diameter. Chickens were exposed to the La Sota vaccine for 30, 60 or 300 s in a closed chamber of the device, thus enabling constant particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The aim of the study was to investigate the immunogenicity of the ZG1999HDS NDV strain applied by means of nebulization and oculonasally to one-day-old layer line chicks. The use of lentogenic strain La Sota by nebulization ( Mazija et al., 2009 , 2010 ) has shown to be simple for application in the hatchery to the newly hatched chicks, and to ensure protection of broiler chickens throughout production. It has also been shown that apathogenic enterotropic strains, such as Ulster 2C and Queensland V4, can be applied deep into the respiratory system without any vaccine reaction, and which also promoted long-term protection ( Mazija et al., 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The aim of the study was to investigate the immunogenicity of the ZG1999HDS NDV strain applied by means of nebulization and oculonasally to one-day-old layer line chicks. The use of lentogenic strain La Sota by nebulization ( Mazija et al., 2009 , 2010 ) has shown to be simple for application in the hatchery to the newly hatched chicks, and to ensure protection of broiler chickens throughout production. It has also been shown that apathogenic enterotropic strains, such as Ulster 2C and Queensland V4, can be applied deep into the respiratory system without any vaccine reaction, and which also promoted long-term protection ( Mazija et al., 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies of vaccine administration by means of nebulization have shown that seroconversion can be expected as early as 14 d in commercial chickens with inherited HI titers ranging from 3.5 to 5 and in SPF chickens as early as 7 d ( Mazija et al., 2009 ; Ervaćinović, 2010 ). In the mentioned study, the titer peak is after 21 d with La Sota strains, while with apathogenic strains with intestinal tropism result in measurable seroconversion in 28 d, with the titer peak 35 d after vaccination ( Mazija et al., 2010 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations